The Effect of Motivation and Discipline Culture Optimalization on Worker’s Work Performance in Buana Tunas Sejahtera Company (Inc.) Kapuas Hulu Regency - Irfan Risyadi; Dewi Kurniati; Anita Suharyani (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2020)
Nowadays, many companies in Indonesia are running in the plantation field. Buana Tunas Sejahtera Company (Inc.) is a palm oil company in West Borneo Province that working under the Kencana Group. This company was organized by leaders, directors, managers, manager assistants, foremen, clerks, permanent workers, and freelance workers. The worker’s work performance in this company was slightly low due to their worker’s low motivation and discipline. This study aimed to know the method to improve the workers’ work performance in Buana Tunas Sejahtera Company (Inc.), Kapuas Hulu Regency. This was a descriptive quantitative study employing an Analytical Hierarchy Process (AHP) done by software namely Expert Choice 11. There were 100 workers chosen by the purposive sampling technique participated in this study. The result showed that the key point in dealing with the worker's work performance issue was meeting their social need, while improving their salary was a key point in dealing with the motivation issue. Building the worker's responsibility was playing an important role in improving the discipline culture. The company needs to improve the worker’s motivation by conducting training sessions, increasing worker’s salaries during the overtime hours, and giving more motivation to their workers. To improve the discipline culture, the company needs to use clear and firm rules to enforce the proper and accountable behavior among the worker.